The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsami.2c19513
|View full text |Cite
|
Sign up to set email alerts
|

Green and Efficient Al-Doped LaFexAl1–xO3 Perovskite Oxide for Enhanced Phosphate Adsorption with Creation of Oxygen Vacancies

Abstract: La-based metal oxide materials are environmentally friendly and show promise for phosphate adsorption. A series of Al-doped perovskite oxides, such as LaFe x Al 1−x O 3 , were prepared using a facile citric acid-assisted sol−gel method. The characterization results demonstrated that with optimized Al doping, there was a significant increase in the specific surface area and increased defect content of perovskite oxide LaFe x Al 1−x O 3 . Adsorption experiments showed that the performance of phosphate removal by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…In the EPR analysis, we observed a prominent peak of increasing intensity for the GNTO samples at g factor = 2.004, corresponding to the oxygen vacancies in the octahedral sites of the lattice. 43 This observation is consistent with the XRD result in Figure 3a, which indicates that oxygen vacancies were created when Ga 3+ ions replaced Ti 4+ ions. The Ga ions inserted near the surface of the NTO particles form surface oxygen vacancies (V OS ), which Yu et al 45 reported for other systems to facilitate the adsorption of reactant gases and thus enhance catalyst performance.…”
Section: Structural Morphological and Compositional Characterization ...supporting
confidence: 90%
See 1 more Smart Citation
“…In the EPR analysis, we observed a prominent peak of increasing intensity for the GNTO samples at g factor = 2.004, corresponding to the oxygen vacancies in the octahedral sites of the lattice. 43 This observation is consistent with the XRD result in Figure 3a, which indicates that oxygen vacancies were created when Ga 3+ ions replaced Ti 4+ ions. The Ga ions inserted near the surface of the NTO particles form surface oxygen vacancies (V OS ), which Yu et al 45 reported for other systems to facilitate the adsorption of reactant gases and thus enhance catalyst performance.…”
Section: Structural Morphological and Compositional Characterization ...supporting
confidence: 90%
“…Previous studies have proposed that oxygen vacancies can be induced in perovskite oxides by doping cations with a lower oxidation state than the host ions. , We looked for evidence of oxygen defects in GNTO and Ru-GNTOs lattice structures using EPR analysis (Figure b). In the EPR analysis, we observed a prominent peak of increasing intensity for the GNTO samples at g factor = 2.004, corresponding to the oxygen vacancies in the octahedral sites of the lattice . This observation is consistent with the XRD result in Figure a, which indicates that oxygen vacancies were created when Ga 3+ ions replaced Ti 4+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, as a new adsorbent material, only three existing studies are available on the phosphate adsorption of perovskites. 9,10 These studies reported that phosphate adsorption is greatly affected by the pH of water due to La-based perovskites Lewis acidic properties and OH − competition under alkaline conditions. The phosphate adsorption performance is excellent under acidic conditions, and the phosphate adsorption performance usually decreases under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%